Doha Declaration sebagai Perlindungan Masyarakat atas Akses Obat Esensial di Negara Berkembang Pasca Trips Agreement - Putu Ayu Sriasih Wesna (Kertha Wicaksana, 2020)
This study aims to examine the protective articles in TRIPs related to medicine and how the Doha Declaration has become very important for developing countries in overcoming the problem of access to essential medicines. This study uses normative legal methods with a statute approach and conceptual approach. The analysis shows that based on the provisions in TRIPs there are two flexibility as protective articles of TRIPs to Patents, especially in the field of medicines, namely Parallel Imports, Compulsory Licenses. This is as regulated further in the Doha Declaration of 2001. The compulsory licensing model is a model that provides more benefits to public access to cheap drugs, especially essential drugs. The Doha Declaration contains seven paragraphs which provide an interpretation of Articles 7 and 8 of the TRIPS Agreement. Paragraphs 1-3 are preamble or preamble to the declaration while Article 4-7 is the implementing article (operative). The Doha Declaration provides provisions that can help developing and underdeveloped countries to overcome the impact of patent protection on the health sector stemming from the TRIPS agreement such as parallel imports and compulsory licenses.